HUBUNGAN 3M, OBAT NYAMUK DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS DEMPO PALEMBANG - Gerry Akino; Yazika Rimbawati; Ria Wulandari; Muhammad Romadhon (LPPM STIKes Mitra Adiguna, 2026)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by dengue virus infection transmitted through the bite of the Aedes aegypti mosquito. This disease remains a serious public health problem because it can lead to fatal conditions and even death if not treated promptly. Simple preventive measures can be carried out through the 3M behavior, namely draining water storage containers, covering water containers to prevent mosquito breeding, and reusing or recycling used items. In addition, the use of mosquito repellent is also considered effective in reducing the risk of mosquito bites that cause DHF. This study aimed to determine the relationship between 3M behavior and the habit of using mosquito repellent with the incidence of DHF in the working area of Dempo Public Health Center, Palembang City, in 2025. This study used an observational analytic approach with a cross-sectional design. The sample consisted of 30 respondents selected using purposive sampling technique. Data were collected through questionnaires and observations, then analyzed using the chi-square test. The results showed that there was a significant relationship between 3M behavior and the incidence of DHF (p-value 0.001 < 0.05). Likewise, the use of mosquito repellent was significantly associated with the incidence of DHF (p-value 0.0002 < 0.05). Consistency in implementing 3M behavior accompanied by the use of mosquito repellent can reduce the risk of DHF.